1982
DOI: 10.1111/j.1365-2923.1982.tb01216.x
|View full text |Cite
|
Sign up to set email alerts
|

The ATP 30-a scale for measuring medical students' attitudes to psychiatry

Abstract: The development and validation of a thirty item, Likert-type scale designed to measure medical students' attitudes to psychiatry-the ATP-30 (Attitudes Toward Psychiatry-30 items)-are described. We had hoped to demonstrate that 'attitude to psychiatry' was not a unitary matter but an amalgam of attitudes to a number of things to do with psychiatric practice. This hope was not fulfilled, as a unitary dimension was obtained. A positive change in the attitudes of students toward psychiatry was demonstrated in thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
184
1
5

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(202 citation statements)
references
References 7 publications
(6 reference statements)
11
184
1
5
Order By: Relevance
“…psychiatric problems (Burra et al 1982;Sloan et al 1996;Strebel et al 2000). Attitudes of female students were more positive than those of male students (Baptista et al 1993;Kuhnigk et al 2007).…”
Section: Practice Pointsmentioning
confidence: 88%
See 3 more Smart Citations
“…psychiatric problems (Burra et al 1982;Sloan et al 1996;Strebel et al 2000). Attitudes of female students were more positive than those of male students (Baptista et al 1993;Kuhnigk et al 2007).…”
Section: Practice Pointsmentioning
confidence: 88%
“…Furthermore, it has been shown that attitudes are related to speciality; yet, it still remains unclear whether professional socialization reinforces existing attitudes or whether existing attitudes result in speciality preference (Batenburg et al 1999). (3) Effects of medical curriculum on attitudes towards psychiatry: A positive change in attitudes towards psychiatry in medical students could be shown most often after their exposure to psychiatry and completion of psychiatric courses (Burra et al 1982;Chung & Prasher 1995;Sloan et al 1996). However, this effect declined significantly over time during undergraduate training (Baxter et al 2001;Altindag et al 2006).…”
Section: Practice Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…the ATP-30 [37] or Balon et al 's [38] questionnaire to measure students' attitudes towards psychiatry or instruments measuring the effect of a rotation on a future career choice in psychiatry). According to El-Gilany et al, [39] '[e]xisting literature … suggests that the quality of the psychiatry clerkship during medical school may be the most important modifiable influence on recruitment into psychiatry. '…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%